Development and Evaluation of Portable Oil Density Scale Device - Santiago Jr, Cereneo Sailog; Alabanza, Jared Espinas; Ambalada, Alleana Rae Villar; Gatil, Carla Mae Villanueva (International Journal of Computing Sciences Research; Vol 3 No 3 (2019): Vol 3, No 3, 2019)
Purpose – The study was designed to develop a Digital Oil Density Scale Device for collecting oil density that would help environmentalist gather needed data in a shorter period of time. The Digital Oil Density is capable of checking the oil sample through a liquid sensor and weighs the oil density present in a water powered by a power bank that supplies 2000mA. The result is displayed in the unit of gram per cubic centimeter (g/cm3). A hard copy of the result can be produce using built in thermal printer. Method – To gather preliminary information, the researchers conducted interviews and group discussion with the end users from the Department of Environment and Natural Resources (DENR) and local Municipal Environment and Natural Resources Office (MENRO). Related studies and literatures were reviewed and hardware and software specifications were identified in the development of the device. In the development process, the agile model was used.  The descriptive design was employed through a purposive sampling of (n=60) evaluators from two groups of respondents; environment workers as Subject Matter Experts (SME) and Information Technology (IT) experts from the academe and the industry. Result – The evaluation of the Digital Oil Density device was patterned after TUP evaluation instrument for hardware prototype consisted of Functionality, Durability, Economy, Safety and Saleability. The overall result obtained was “very good” cut across the two (2) groups of evaluators; environmentalists and IT experts. The functionality test exhibited ease of operation and convenience in using the device. More so, the device safety exhibited absence of faulty from electricity, sharp edges and a provision for device protection is present. Conclusion – The developed device for collecting oil density samples have meet all requirements in terms of all needed functions and characteristics.  The device lessened the time and effort needed to transport oil samples to distant laboratories with its compact size and portability. It gives results at the same time of testing of oil for its density.  Recommendations – The researchers recommend that an internal power supply and a solid carrying case for easier portability may be built. The users from the DENR and MENRO shall undergo capability training to properly equip with the functionalities of the device. The researchers also suggest that a future research can be conducted such as assessing the efficiency of the device. Research Implication – The Digital Oil Density device is useful and can be a great help to not only environmentally concerned citizens but also it can teach other potential users to be aware of the dangers when oil is present in water.  The use of this technology can synergize the academe and the environment sector in working together in addressing environmental issues.